2021
DOI: 10.5194/piahs-384-213-2021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation de deux méthodes de correction de biais des sorties de modèles climatiques régionaux Cordex-Africa pour la prévision des pluies  : cas du bassin côtier oranais

Abstract: Abstract. Ce travail vise à évaluer les pluies simulées issues des sorties de modèles climatiques régionaux Cordex-Africa dans le bassin côtier oranais en Algérie. Pour cela les simulations du modèle RCA4 (Rossby Centre Atmosphere model, version 4) forcé par deux modèles de circulation globale (MPI-ESM-LR et CNRM-CM5) sous deux scenarios de forçages radiatifs «Representative Concentration Pathways» (RCPs) RCP 4.5 et RCP 8.5 sont comparées aux pluies observées au niveau de cinq stations pluviométriques, au cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The Qmap package found in the R software and implemented by (Gudmundsson et al 2012) was used to apply this quantile-quantile bias correction. The performance of the correction was then evaluated on the basis of the calculation of the bias of the corrected simulated data compared to the observed data using equation 1 (Taïbi et al 2021)…”
Section: Calibration Of the Chosen Climate Modelmentioning
confidence: 99%
“…The Qmap package found in the R software and implemented by (Gudmundsson et al 2012) was used to apply this quantile-quantile bias correction. The performance of the correction was then evaluated on the basis of the calculation of the bias of the corrected simulated data compared to the observed data using equation 1 (Taïbi et al 2021)…”
Section: Calibration Of the Chosen Climate Modelmentioning
confidence: 99%
“…According to the two future scenarios, [47] discovered that drought episodes in the northwest areas are anticipated to be more severe and of longer lengths than in the past, particularly during the hot season (between May and September) between 2021 and 2071. Taïbi et al [48] discovered that the availability of surface water collected at the Ain Dalia dam in northeastern Algeria is likely to decline by 5% to 13% by 2050 and by 21% to 44% by 2100. Hadour et al [49] found similar results in some basins in the northwestern Algeria region, and Zeroual et al [50] found similar results in the Algerian-Hodna-Soummam basins.…”
Section: Change In Streamflowmentioning
confidence: 99%